The Effect of Special Exercises on the Development of Some Physical abilities and Basic Skills in Deaf Futsal Players - Abbas, Amir; Khadem, Muhammed (Journal of Physical Education, 2020)
The research aimed at identifying the effect of special exercises on some physical and skill abilities in deaf futsal players. The researchers used the experimental method on deaf futsal players from the Babel governorate. The experimental program was applied for (10) weeks with (3) training sessions per week with high-intensity interval training using training aids. The data was collected and treated statistically to come up with the conclusions. The researchers concluded that the proposed training program developed physical and skills abilities in the subject under study. Finally, they recommended training players according to the physical abilities of players so as to gain better conditioning and development in motor behavior in the subject under study.